Impact of China on trade in electronic products. Issue 2 (18th June 2021) - Pham, Cong S.; Lovely, Mary E.; Nguyen, Xuan; Chao, Chi‐Chur
Abstract: Using 6‐digit product‐level data of exports in electronics, this paper finds robust evidence that China's exports adversely affect both the intensive export margin and the extensive export margin of its competitors for the 1992–2018 period. The displacement effects of China's exports on the intensive margin apply especially for the group of intermediate and capital electronic goods and are much more robust and significantly larger in magnitude than the displacement effects found in other studies using aggregated trade data. Finally, we find that China's displacement effect is increasing in China's advantage relative to its competitors in terms of human capital index and internet access of its population.